CHOOL RELATED FACTORS INFLUENCING EFFECTIVE IMPLEMENTATION OF GRADE ONE COMPETENCY BASED CURRICULUM IN MBOONI EAST SUBCOUNTY, MAKUENI COUNTY, KENYA - NGUVI, MARIA NDOLO (MksU Press, 2023)
The purpose of this study was to investigate school related factors influencing effective implementation of competence-based curriculum in Mbooni East Sub-County, Makueni County, Kenya. The study was guided by the following objectives: To determine the extent to which teacher characteristics influence effective implementation of competency-based curriculum; examine the extent to which the application of CBC pedagogy influences effective implementation of competency based curriculum; assess the extent to which learning support resources influences effective implementation of competency based curriculum; and evaluate the extent to which teacher’s instructional support influences effective implementation of competency based curriculum in Mbooni East Sub-County, Makueni County. This study was guided by the Curriculum Implementation Theory and the Technology, Pedagogy and Content (TPACK) Model. The theory postulates that the success of any education programme is determined by the management of the support facilities, the teacher’s ability and the clarity of the implementer. The model underscores role of Information Communication Technology and content mastery in implementation of any new educational programme. The study adopted a descriptive survey design and targeted a sample size of 77 respondents, who included head teachers, grade one teachers and the curriculum support officers from Mbooni East Sub-County, Makueni County using random sampling and census sampling techniques. A pilot study was done using 11 respondents from non-participating schools in the neighbouring Mwala subcounty. The research instrument included questionnaire, an interview guide and an observation checklist. Subject experts, were used to check the validity of the research instruments while test-retest technique was used to ascertain the reliability of the questionnaire. The researcher personally collected data using the drop-and-pick method for questionnaires, conducted interviews to key informants and also filled the observation checklist. Data was analyzed using both qualitative and quantitative techniques. Qualitative data was analyzed thematically along the specific objectives and presented in narrative forms whereas the quantitative data was analyzed descriptively using frequencies and percentages with the help of Statistical Packages for Social Sciences (SPSS Version 24) and presented using tables, charts and graphs.